Keadilan Restoratif dalam Penyelesaian Tindak Pidana Pemalsuan Surat pada Perjanjian Kredit: Studi Kasus BPR NBP 24 Duri - Riko Slamat Tampati; Sriono Sriono; Wahyu Simon Tampubolon; Indra Kumala Sari (MAN 4 Kota Pekanbaru, 2026)
This study analyzes the shift from punitive to restorative paradigms in resolving document forgery within banking credit agreements. Using an empirical legal approach, the research evaluates how restorative justice mechanisms effectively address fraud involving dual collateral documents at BPR NBP 24 Duri. The findings reveal that document forgery in this context is not merely a breach of contract but a systemic failure in collateral verification that necessitates legal restoration. The study’s novelty lies in its analysis of the